Factors Influencing STEM Stream Selection Among Form Four Students in Baling District from Cognitive and Psychomotor Aspects - IBRAHIM, MOHAMAD NOR FAIZAL; Rosnee Ahad; Yusmarwati Yusof (Research and Innovation in Technical and Vocational Education and Training, 2025)
This study examines the relationship between cognitive and psychomotor levels of students and the factors influencing their selection of the STEM stream among Form Four students in Baling District. A decline in STEM enrolment and retention rates, particularly in rural areas, necessitates this investigation. The study employs a quantitative approach using a structured questionnaire distributed to 165 stratified random samples from a population of 274 students across nine secondary schools. The instrument was developed based on Bloom’s and Simpson’s Taxonomies to assess cognitive and psychomotor levels. Findings indicate that students exhibit moderate cognitive and psychomotor levels. Interest is identified as the most dominant factor influencing STEM selection, followed by family and peer influence. A significant positive correlation exists between students’ cognitive and psychomotor levels with their STEM stream choices. The study provides insights for educators and policymakers to enhance STEM curriculum design, improve laboratory facilities, and implement project-based learning (PBL) to foster greater student engagement in STEM fields.